Does the Hebrew Bible have anything to say about homosexuality? - Stiebert, Johanna (Old Testament essays, 2001)
The article begins with a reference to Section 9 of the Bill of Rights, which forms an important pan of South Africa's Constitution. This section condemns discrimination on the grounds of gender and sexual orientation. From here the discussion moves on to state that homosexuality is a sexual orientation. It is a sexual orientation, moreover, which is frequently condemned on the grounds of a small number of passages in the Hebrew Bible. This article argues that the Hebrew Bible does not make reference to and hence, does not condemn homosexuality. While some sort of sexual act between two men is prohibited, homosexuality as a sexual orientation receives no mention. The article contains a discussion on the social construction of masculinity and (to a lesser extent) femininity, with reference to the two narrative accounts in Genesis 19 and Judges 19. This is followed by a detailed analysis of the laws of Leviticus 18:22 and 20:13.